AN INVALUABLE EDUCATION: LOOKING AT POVERTY AND PROSPERITY WITH THE RIGHT PERSPECTIVE - Ester Gratia Siregar; Dermawati Purba; Rifka Napitupulu; Lewina Karine Tampubolon (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze and describe how poverty and prosperity were in the time of Old Test. Poverty and prosperity became very important because they had a wide interrelationship in the life of the Israelites. In the Bible we find that the factors both generating wealth and poverty are the same as those seen in general. In his poverty, people are still taught to make offerings and share blessings with others and also to pay attention to the life of the priest. Prosperity theology or prosperity theology (English: prosperity theology or prosperity gospel), sometimes also called successful theology, is a Christian theology that teaches that prosperity and success (rich, successful, and perfectly healthy) are external signs from God for his loved ones. Furthermore, at the end of this paper it will be concluded that Poverty and Prosperity that the standard of poverty and prosperity is not material from God.